ANALISIS PERTIMBANGAN HAKIM MENGENAI GANTI RUGI TERHADAP DAMPAK PENCEMARAN LINGKUNGAN YANG DILAKUKAN OLEH PT GREENFIELDS FARM 2 BLITAR (Putusan Perkara Nomor 77/Pdt.G/LH/2021/PN Blt) - Sokheh, Mohammad Hidayatus; Nurbaedah, Nurbaedah (Universitas Islam Kadiri, 2025)
This research analyzes the fulfillment of compensation for the impact of waste pollution which results in environmental damage. Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management gives the government and/or regional governments, communities and environmental organizations the right to file a lawsuit for compensation losses due to environmental pollution and/or damage. This research aims to find out how compensation for environmental damage carried out by PT Greenfields Farm 2 Blitar is fulfilled and what are the inhibiting factors in fulfilling compensation for acts of environmental pollution. This research uses normative legal research methods. The research results show that there is a reference in calculating the amount of compensation which can only be determined by an expert on the basis of Minister of the Environment Regulation Number 7 of 2014 concerning Environmental Losses Due to Environmental Pollution and/or Damage.